Analysis of Factors That Influence the Quality of Financial Reports at the TPI Belawan Class II Immigration Office - Amanda Naibaho; Dito Aditia Darma Nasution (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this research is to conduct an analysis of the Internal Control System, Implementation of Government Accounting Standards, Utilization of Information Technology, Quality of Human Resources on the quality of financial reports at the TPI Belawan Class II Immigration Office. This research is included in Quantitative research, with data collection carried out by distributing questionnaires to all employees at the TPI Belawan Class II Immigration Office using the purposive sampling method. The data that has been collected is then processed using IBM SPSS 21 computer software. Hypothesis testing uses statistical methods, namely multiple linear regression analysis. Based on the results of hypothesis testing, it shows that the Internal Control System, Implementation of Government Accounting Standards, Utilization of Information Technology, Quality of Human Resources has a positive and significant effect on the quality of financial reports at the TPI Belawan Class II Immigration Office. Therefore, agency leaders must consider the Internal Control System, Implementation of Government Accounting Standards, Utilization of Information Technology, Quality of Human Resources in determining decision making and policies related to the quality of the financial reports of the TPI Belawan Class II Immigration Office.